1999
DOI: 10.1063/1.371458
|View full text |Cite
|
Sign up to set email alerts
|

Determination of diffusion in polycrystalline platinum thin films

Abstract: Grain boundary diffusion of titanium through platinum thin films has been carried out in the temperature range from 200 to 600°C. Five different platinum/titanium bilayer thicknesses, from 35 to 800 Å Pt, were annealed in 5% O 2 /95% N 2 . The accumulation of titanium at the platinum surface layer was measured by x-ray photoelectron spectroscopy ͑XPS͒ to determine the grain boundary diffusion coefficient (D b ). Diffusivity values were calculated based on two different analysis methods assuming type C kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…3) showed that the density of threading dislocations (labeled "O" and "A" in Fig. 3) was in the order of 5¥10 SIMS showed that the Pt electrodes on the Ti adhesion layers contained Ti, consistent with findings by others [18][19][20]. The influence of Ti underneath (111) textured Pt electrodes on perovskite film texture is well documented [21,22].…”
Section: A Srtio 3 Thin Film Microstructuresupporting
confidence: 81%
“…3) showed that the density of threading dislocations (labeled "O" and "A" in Fig. 3) was in the order of 5¥10 SIMS showed that the Pt electrodes on the Ti adhesion layers contained Ti, consistent with findings by others [18][19][20]. The influence of Ti underneath (111) textured Pt electrodes on perovskite film texture is well documented [21,22].…”
Section: A Srtio 3 Thin Film Microstructuresupporting
confidence: 81%
“…The other systems studied would be expected to exhibit appreciably higher interdiffusion based on their lower solidus temperatures [14]. For example, DiBattista and Schwank [15] examine diffusion of Ti in Pt thin films and report a range of diffusivities which are reasonably consistent with the diffusivity of cm we extract from the diffusion lengths associated with the gradual transition observed in the work function measurements. Measurements in the Nb/W system show a diffusivity of around times smaller [13].…”
Section: Resultsmentioning
confidence: 69%
“…Note that L/L = 0 when surface diffusion is dominant since this is a non-densifying diffusion mechanism. Based on extrapolations to room temperature from previously measured values of the diffusivities at higher temperatures, we expect surface diffusion to dominate for Pt at or near room temperature since the surface diffusivity is at least many orders of magnitude faster than other diffusivities and the surface areas are also much higher for nanoparticles compared to bulk materials [12][13][14][15].…”
Section: Theoretical Considerationsmentioning
confidence: 99%